MYB-NFIB gene fusion in prostatic basal cell carcinoma: clinicopathologic correlates and comparison with basal cell adenoma and florid basal cell hyperplasia - Magers, Martin J; Iczkowski, Kenneth A; Montironi, Rodolfo; Grignon, David J; Zhang, Shaobo; Williamson, Sean R; Yang, Ximing; Wang, Mingsheng; Osunkoya, Adeboye O; Lopez-Beltran, Antonio; Hes, Ondrej; Eble, John N; et al. (Modern pathology, 2019)
Prostatic basal cell carcinoma is a malignant neoplasm composed of basaloid cells forming infiltrative nests and tubules, which may potentially be misdiagnosed as benign basal cell proliferations (i.e., florid basal cell hyperplasia or basal cell adenoma) and also closely resembles adenoid cystic carcinoma of the salivary gland. MYB-NFIB gene rearrangement occurs in 30-86% of salivary gland adenoid cystic carcinomas. We sought to further characterize MYB gene rearrangement in prostatic basal cell carcinoma and correlate MYB-NFIB fusion status with other clinicopathologic characteristics. To this end, FISH analysis for MYB-NFIB gene fusion using fusion probes was performed on formalin-fixed, paraffin-embedded tissue sections from prostatic basal cell carcinoma (n = 30), florid basal cell hyperplasia (n = 18), and basal cell adenoma (n = 4). Fourteen of 30 (47%) cases of basal cell carcinoma were positive for MYB-NFIB gene fusion FISH, and no cases of benign basal cell proliferations were positive (p < 0.05). FISH-positive patients (mean age = 63 years, range: 35-81) tended to be younger than FISH-negative patients (mean age = 70 years, range: 55-93). Most FISH-positive cases demonstrated adenoid cystic carcinoma-like morphology (57%), and most FISH-negative cases demonstrated nonadenoid cystic carcinoma-like morphology (93%); one case (FISH-positive) demonstrated areas with both adenoid cystic carcinoma-like and nonadenoid cystic carcinoma-like morphology. FISH-positive cases more frequently demonstrated perineural invasion (50% vs. 14%, p < 0.05) compared to FISH-negative cases. Conversely, tall basal cells (i.e., neoplastic cells at least two times taller than wide) were more frequent in FISH-negative cases than FISH-positive cases (93% vs. 36%, p < 0.05). Approximately, 50% of prostatic basal cell carcinoma harbor MYB-NFIB gene fusion. The majority of these cases were characterized by adenoid cystic carcinoma-like morphology, perineural invasion, and lack tall basal cells. Florid basal cell hyperplasia and basal cell adenoma are negative for MYB-NFIB gene fusion.
Keywords: dospělí; Adenoma; bazocelulární karcinom; Adult; adenom; fúzní onkogenní proteiny; lidé; Oncogene Proteins, Fusion; hyperplazie; Aged, 80 and over; nádory prostaty; Prostatic Neoplasms; Male; Aged; Carcinoma, Basal Cell; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Hyperplasia; Middle Aged; Humans